The impact of diverse student backgrounds and flexible delivery modes on assessment outcomes - Xia, Jianhong (Cecilia); Yeo, S. (Edith Cowan University, 2010)
Managing the diversity of student backgrounds in today's complex higher education classrooms is a challenging task for lecturers. This paper reports on action research involving a complex nested group of units in Geographic Information Science (GIS) delivered to a diverse student body, including international and domestic students from different disciplines studying in on-campus, online and distance education modes. GIS is a technology-dependent discipline of relevance to a wide variety of other disciplines including, for example land management, urban development or health sciences, to facilitate land-use planning, map disease distribution, analyse spatial patterns of crime or model urban growth. The concern of the lecturer was that adaptation of the learning activities necessary for accommodating flexible modes of delivery and student backgrounds would impact on student assessment outcomes. The research findings indicate that while there were some significant differences in assessment outcomes associated with student backgrounds and discipline, no differences could be ascribed to, for example, language background of students. This paper discusses the study and seeks explanations for the results. The implications for teaching and further action research with this unit in order to sustain student numbers and teaching and learning standards in the future are also presented.